Carboniferous–Early Permian sedimentary rocks from the north‐eastern Erenhot, North China: Implications on the tectono‐sedimentary evolution of the south‐eastern Central Asian Orogenic Belt. (3rd February 2020) - Ji, Zejia; Zhang, Zhicheng; Yang, Jinfu; Chen, Yan; Tang, Jianzhou
Abstract : Reconstructing the Late Palaeozoic tectonic process of the Hegenshan Ophiolite Belt is critical for evaluating the protracted accretion and collision history of the south‐eastern Central Asian Orogenic Belt. The Carboniferous–Permian sedimentary rocks near the Erenhot area are key to revealing the evolutionary history of the Hegenshan Ocean. In this study, new stratigraphic, geochemical, and detrital zircon U–Pb age analyses were conducted on three Carboniferous–Early Permian strata (viz., Halatumiao, Amushan, and Benbatu formations). Deposition of the Halatumiao Formation began around 313 Ma, inferred from a zircon U–Pb age from a lower tuff layer. The end of deposition is constrained by two later intrusive high‐K granite plutons that give ages of 277–285 Ma. The predominant detrital zircon group in these strata is characterized by ages of 340–290 Ma, high positive εHf (t) values, and juvenile TDM2 ages, which suggest adjacent and unitary juvenile provenances. The Halatumiao Formation mainly consists of blackish fine‐grained sedimentary rocks with a thickness of 6–7 km implying a high sedimentation rate and a stable hydrodynamic condition. Thus, the Halatumiao Formation most likely indicates the existence of a deep and wide ocean basin under an effect of long‐lived and continuous extension. The Amushan Formation has a comparable depositional age to the Halatumiao Formation, based on three detrital zircon Palaeozoic age populations with peaks of 317, 389, and 441 Ma, but contains more complex provenances. The Benbatu Formation has an earlier deposition age between ca. 324 and 314 Ma. Its detrital zircons yield a predominant age group at around 410–440 Ma but lack syn‐sedimentary Late Palaeozoic age. Unlike the Halatumiao Formation, the two other formations are considerably smaller in terms of their deposition thickness and outcrop area. The transition from Benbatu to Amushan and Halatumiao formations records the development of a gradually deeper and wider ocean basin in response to a back‐arc extensional setting from the Late Carboniferous to the Early Permian.